Monitoring of Harmful Algal Bloom (HAB) of Noctiluca scintillans (Macartney) along the Gulf of Mannar, India using in-situ and satellite observations and its impact on wild and maricultured finfishes. (March 2023) - Rameshkumar. P,; Thirumalaiselvan, P.S.; Raman, Mini; Remya, L.; Jayakumar, R.; Sakthivel, M.; Tamilmani, G.; Sankar, M.; Anikuttan, K.K.; Menon, N. Nandini; Saravanan, Raju; Ravikumar, T.T.; et al.
Abstract: In the Gulf of Mannar, Noctiluca scintillans blooms have been observed three times in September 2019, September and October 2020, and October 2021. It was determined and measured how the bloom period affects ichthyo-diversity. Noctiluca cell density varied slightly from year to year, ranging from1.8433 × 10 3 cells/L to 1.3824 x 10 6 cells/L. In surface and sea bottom waters, high ammonia levels and low dissolved oxygen levels were noted. During the bloom period a significant increase in chlorophyll concentration was found. The amount of chlorophyll in GOM was extremely high, according to remote sensing photos made using MODIS-Aqua 4 km data. Acute hypoxia caused the death of wild fish near coral reefs and also in fish reared in sea cages. The decay of the bloom resulted in significant ammonia production, a dramatic drop in the amount of dissolved oxygen in the water, and ultimately stress, shock, and mass mortality of fishes. Highlights: Harmful Algal Bloom incidents were recorded frequently over the past three years After ten years, a Noctiluca scintillans bloom has been seen in the GoM. Fish raised in cages and wild fishes on coral reefs were both found dead from severe hypoxia. By using near real-time ocean colour determined chlorophyll concentration model derived current patterns it will be possible to alert cage culture farmers